2017
DOI: 10.1097/aap.0000000000000703
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Morphine for Laparoscopic Segmental Colonic Resection as Part of an Enhanced Recovery Protocol

Abstract: Background and ObjectivesManagement of postoperative pain after laparoscopic segmental colonic resections remains controversial. We compared 2 methods of analgesia within an Enhanced Recovery After Surgery (ERAS) program. The goal of the study was to investigate whether administration of intrathecal bupivacaine/morphine would lead to an enhanced recovery.MethodsA single-center, randomized, double-blind controlled trial was performed (NL43488.101.13). Patients scheduled for laparoscopic segmental intestinal res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 24 publications
(33 reference statements)
1
60
2
Order By: Relevance
“…The SFS with analgesia may be the most important factor when opting for postoperative analgesia. As many as 96% of the group A patients assessed analgesia as excellent, whereas only 20% of those from group B were of that opinion, which is in discrepancy with a similar study which showed almost equal satisfaction of patients with analgesia [29].…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…The SFS with analgesia may be the most important factor when opting for postoperative analgesia. As many as 96% of the group A patients assessed analgesia as excellent, whereas only 20% of those from group B were of that opinion, which is in discrepancy with a similar study which showed almost equal satisfaction of patients with analgesia [29].…”
Section: Discussioncontrasting
confidence: 88%
“…Itching is often mentioned in literature as a frequent side effect of intrathecal morphine, particularly in obstetrics, where gestation hormones may lead to certain changes on opioid receptors [28]. Some researchers from the Netherlands have shown that intrathecal administration of morphine for laparoscopic colon resection is followed with itching more often [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multimodal analgesic regime minimising opioid use has been shown to enhance recovery 2 30. ITM has become a well-documented component in several ERAS protocols29 31–34 and a protocol for a systematic review of ITM in abdominal and thoracic surgery patients has recently been published 35. Despite the higher rating of NRS at mobilisation during the first few days in the ITM group, the consumption of opioids was nearly three times lower in the same time period compared with the EDA group, and the QoL index did not differ between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…A single dose of 100-300 µg produces analgesia that lasts over 24 hours. 1,2 However the fear for late respiratory depression typically occurring 6-11 hours after administration 3 limits the use of Intrathecal morphine.…”
Section: Introductionmentioning
confidence: 99%